The brothers of Auschwitz - Adler, Malka, 1945- (London : One More Chapter, 2020)
"Dov and Yitzhak live in a small village in the mountains of Hungary, isolated both from the world and from the horrors of the war. But one day in 1944, everything changes. The Nazis storm the homes of the Jewish villagers and inform them they have one hour. One hour before the train will take them to Auschwitz. Six decades later, from the safety of their living rooms at home in Israel, the brothers finally break their silence to a friend who will never let their stories be forgotten."--Publisher.
"P.S. insights, interviews & more..." follows the text.
Keywords: Auschwitz (Concentration camp) -- Fiction; Families -- Hungary -- Fiction; Brothers -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Survival -- Fiction; Reminiscing in old age -- Fiction; War stories; Hungary -- History -- 20th century -- Fiction; Israel -- Fiction; Historical fiction